Identification of Functional Determinants in the Chikungunya Virus E2 Protein. - Christopher Weber; Eva Berberich; Christine von Rhein; Lisa Henß; Eberhard Hildt; Barbara S Schnierle (Public Library of Science (PLoS), 2017)
BACKGROUND:Chikungunya virus (CHIKV) is a mosquito-transmitted alphavirus that causes high fever, rash, and recurrent arthritis in humans. It has efficiently adapted to Aedes albopictus, which also inhabits temperate regions, including Europe and the United States of America. In the past, CHIKV has mainly affected developing countries, but has recently caused large outbreaks in the Caribbean and Latin America. No treatment or licensed CHIKV vaccine exists. METHODOLOGY/PRINCIPAL FINDINGS:Here, we have identified determinants in the CHIKV cell-attachment protein E2 that facilitate cell binding. The extracellular part of the E2 gene is subdivided into the three domains, A, B, and C. These domains were expressed in E. coli and as Fc-fusion proteins generated from HEK293T cells and used for cell-binding assays. Domains A and B bound to all cells tested, independently of their permissiveness to CHIKV infection. Domain C did not bind to cells at all. Furthermore, CHIKV cell entry was promoted by cell-surface glycosaminoglycans (GAGs) and domain B interacted exclusively with GAG-expressing cells. Domain A also bound, although only moderately, to GAG-deficient cells. Soluble GAGs were able to inhibit CHIKV infection up to 90%; however, they enhanced the transduction rate of CHIKV Env pseudotyped vectors in GAG-negative cells. CONCLUSION/SIGNIFICANCE:These data imply that CHIKV uses at least two mechanisms to enter cells, one GAG-dependent, via initial attachment through domain B, and the other GAG-independent, via attachment of domain A. These data give indications that CHIKV uses multiple mechanisms to enter cells and shows the potential of GAGs as lead structures for developing antiviral drugs.